Study of the Role of Information and Communication Technology (ICT) in Remote Work during and after COVID-19 (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The COVID-19 pandemic accelerated the adoption of remote work practices globally, transforming the role of Information and Communication Technology (ICT) in facilitating these new work arrangements. This paper explores how ICT enabled remote work during the pandemic and examines its enduring impact post-pandemic. Key ICT tools, their effectiveness, challenges, and future prospects are analyzed through data from various studies and surveys. The findings underscore the crucial role of ICT in maintaining business continuity, reshaping organizational structures, and enhancing work-life balance, while also highlighting issues like digital divide, security, and productivity concerns.